Succession of splicing regulatory elements determines cryptic 5΄ss functionality - Brillen, Anna-Lena; Schöneweis, Katrin (Nucleic acids research, 2017)
Abstract. A critical step in exon definition is the recognition of a proper splice donor (5΄ss) by the 5’ end of U1 snRNA. In the selection of appropriate 5΄ss